2023
DOI: 10.1177/15593258231179904
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Actions of Two Separated Aqueous Extracts From Arbutus (Arbutus unedo) and Hawthorn (Crataegus monogyna) Fruits Against High-Fat Diet in Rats via Potent Antioxidant Target

Soumaya Wahabi,
Kais Rtibi,
Amal Atouani
et al.

Abstract: Arbutus unedo and Crataegus monogyna are widely distributed throughout the Mediterranean basin and commonly used in folk medicine against a wide range of diseases. Therefore, the present study has been designed to evaluate the anti-obesity potential of two aqueous extracts of the fruits of A. unedo (AUAE) and C. monogyna (CMAE). Male Wistar rats were supplied with a standard diet (SD), high-fat diet (HFD), HFD with the two separated extracts at the same dose (300 mg/kg, BW, p. o.), or HFD with atorvastatin-(AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…The A. unedo extracts effectively reduced lipid peroxidation in the irradiated protozoa, with the aqueous fruit extract having a slightly lesser effect (Table 2). This plant is rich in polyphenol and flavonoid compounds (Wahabi et al 2023), which possess antioxidant and radioprotective properties (Dowlath et al 2021). The DPPH test confirmed that the extracts had considerable scavenging activity, with the flower extracts exhibiting higher activity than the fruits.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The A. unedo extracts effectively reduced lipid peroxidation in the irradiated protozoa, with the aqueous fruit extract having a slightly lesser effect (Table 2). This plant is rich in polyphenol and flavonoid compounds (Wahabi et al 2023), which possess antioxidant and radioprotective properties (Dowlath et al 2021). The DPPH test confirmed that the extracts had considerable scavenging activity, with the flower extracts exhibiting higher activity than the fruits.…”
Section: Discussionmentioning
confidence: 92%
“…Because of its nutritional and medicinal values, several studies have investigated the composition of different extracts of A. unedo. The plant is an important source of phytochemicals, bioactive compounds (phenols, anthocyanins, triterpenes, iridoids, sterols), vitamins, minerals, essential fatty acids, and dietary fiber, which gives it interesting biological activities such as antioxidant, anti-inflammatory, antimicrobial and other activities (Wahabi et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In adipocytes, apoptosis worsens obesity by increasing macrophage infiltration into adipose tissue 20 . Therefore, recent studies attempt to attenuate obesity through antioxidative treatments 21 , 22 . Similarly, in this study, SHWE and F-SHWE both possessed oxygen radical scavenging effects comparable to ascorbic acid, a commercially used antioxidant (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Crataegus fruits have been found to possess several biological effects, like antiobesity 17 antiproliferative, antitumor, anti‐inflammatory, and apoptosis‐inducing activities, among others, which could be associated with their polyphenols content 8,13,18,19 . Phenolic compounds are the principal bioactive compounds in Crataegus and Sorbus species 16,20 .…”
Section: Introductionmentioning
confidence: 99%